Alexander Disease in Israel: Megalencephaly and Leukoencephalopathy and Its Differential Diagnosis - Mahajnah, Muhammad; Abu-Rashid, Muhammad; Lerman-Sagie, Tally; Goikhman, Igor; Zelnik, Nathanel (Journal of Pediatric Neurology, 2015)
Alexander disease (AD) is a rare leukodystrophy caused by overexpression of glial fibrillary acidic protein and heat shock proteins, which accumulate in the astrocytes and appear as Rosenthal fibers. Clinically, there are three main phenotypes: infantile, juvenile, and adult forms, with a highly variable clinical course. The classical, and most common phenotype, is the infantile form, which occurs during the first 2 years of life. The diagnosis of AD is based on clinical findings and, supported by magnetic resonance imaging, should be suspected in infants with leukoencephalopathy associated with progressive megalencephaly. In this article, we report two additional patients. Their mutations were already reported; however, while one of them is a common hotspot of the severe infantile-onset phenotype, the other is uncommon and was not yet reported in early infantile-onset AD. To the best of our knowledge, these are the first cases of AD reported from Israel. AD was reported anecdotally in a few other Middle Eastern countries but, since they are usually de novo sporadic mutations, they are not affected by consanguineous marriages, and do not tend to cluster in isolated ethnic populations.
Keywords: Alexander disease; glial fibrillary acidic protein; megalencephaly; Canavan disease; megaloencephalic leukoencephalopathy